An investigation on the type of refurbishment works in UiTM Shah Alam / Mohd Hanif Awang - Awang, Mohd Hanif (Faculty of Architecture, Planning and Surveying, 2010)
The transformation ITM becomes to be UITM there are many thing are to be transform especially transform on that building. The refurbishments are carried out in transformation of ITM become UITM but at the same time there are problem occur from the refurbishment work. The study has a specific objective to achieve in the end. The primary of objective is to identify the type of refurbishment work carried out in UITM Shah Alam from years 2001 to 2009. Second objective to categorize type of refurbishment carried out in UITM Shah Alam from years 2001 to 2009 and the third objectives is to evaluate the performance of refurbishment work to meet the user needs. This dissertation include the outline of introduction and to the subject each topic, this dissertation also include the statistic type of refurbishment carried out in UITM Shah Alam and also the category type of refurbishment divided by two which is classification by uses and classification by work. Research methodology which had been applied in the six case studies is through observation, and interview involved person in refurbishment work. The analyses of questionnaire are to define in this dissertation to ensure the level of safety and quality of refurbishment work are carried out in UITM Shah Alam. Finally, conclusion from the research finding and the recommendation are be made in the last chapter to improve the performance of refurbishment work to meet the user need.